Welcome to POCUS Journal - Amer M. Johri (CINQUILL Medical Publishers Inc., 2016)
Welcome to the first issue of the world's first journal dedicated solely to point-of-care ultrasound. The Point-of-care Ultrasound Journal (POCUS J) is unique in its dedication to showcasing studies performed by any specialty- whether it's the Emergency Department, Critical Care, Anesthesiology, Cardiology, Primary Care or Allied Health.